Empowerment of Food Traders Regarding Hazardous Additives for Food Towards Healthy Natural Food Products in Tanjung Morawa District - Ginting, Adil; Tarigan, Lina; Ginting, Mimpin; Perangin-angin, Sabarmin; Masmur, Indra (ABDIMAS TALENTA: Jurnal Pengabdian Kepada Masyarakat, 2021)
Food safety issues have become a global concern because hundreds of millions of people suffer from diseases due to contaminated food. Food poisoning cases in Indonesia continue to increase from year to year. In 2013, the POM reported that there were 48 outbreaks (KLB) of food poisoning from 34 provinces in Indonesia. In Tanjung Morawa Subdistrict, especially Mardisan Village, there are many food vendors, ranging from food for breakfast, various snacks during the day to night. In this area there are also many flower sellers, so the village is always busy with flower buyers. In addition to buying flowers, they generally also need food and drinks so that food vendors in this area are also growing. However, very often these food traders do not pay attention to food safety requirements because they are tempted by the maximum profit. For this reason, dedication is carried out to increase the knowledge and skills of traders in processing healthy and natural foods without using additives that are harmful to health. Training was carried out on increasing partners' knowledge in the use of additives permitted by the Minister of Health as an effort to reduce the use of additives that are harmful to health. The training was carried out by using the lecture method, discussion by giving lieaflead to food sellers. The food vendors are very enthusiastic about participating in the training with many questions from the participants about allowed and not allowed food substances. The traders promised to implement natural and healthy food processing methods without using additives that are harmful to health. The head of the food merchant group will monitor the food safety in this area so that natural and healthy food is still sold in Mardisan.